THE IMPACT OF ADVERSITY QUOTIENT AND SELF-EFFICACY ON STUDENTS’ STATISTICAL REASONING ABILITIES: A PILOT STUDY - Rusliah, Nur; Roza, Muthia; Putra, Aan; Fidria Lova, Freti (IAIN Ambon, 2025)
Statistical reasoning skills are essential across various disciplines, as they involve the ability to interpret phenomena, solve problems, and make logical inferences based on statistical data. However, students exhibit varying levels of statistical reasoning, ranging from basic understanding to the ability to interpret and justify conclusions, and these differences are important because they affect how effectively students participate in data-driven learning. Such variation may be shaped by individual factors, including their capacity to manage challenges (adversity quotient) and their confidence in their own abilities (self-efficacy). This study investigates the impact of adversity quotient and self-efficacy on students’ statistical reasoning performance. A total of 38 high school students in Jambi, Indonesia, participated in this correlational study. Data were gathered through questionnaires measuring adversity quotient and self-efficacy, along with a statistical reasoning test. The multiple linear regression analysis showed that both adversity quotient and self-efficacy made significant positive contributions to students’ statistical reasoning. The regression equation Y = 2.909 + 0.152X₁ + 0.046X₂ indicates that an increase in adversity quotient is associated with a 0.152-point rise in statistical reasoning scores, while an increase in self-efficacy corresponds to a 0.046-point rise. The coefficient of determination (R² = 0.595) suggests that these two variables together explain 59.5 percent of the variance in students’ statistical reasoning. These findings suggest that educators should foster both adversity quotient and self-efficacy to enhance students’ statistical reasoning skills, For example, through challenging statistics assignments, constructive feedback, and a learning environment that encourages persistence. In addition, teachers need to consider other variables that may influence learning outcomes.